Crossdressing to Backbeats: The Status of the Electroclash Producer and the Politics of Electronic Music - Madden, David (Dancecult, 2012)
Addressing the international emergence of electroclash at the turn of the millenium, this article investigates the distinct character of the genre and its related production practices, both in and out of the studio. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers, or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music, where the role of the producer has typically been associated with men. These changes are discussed in relation to the way electroclash producers Peaches, Le Tigre, Chicks on Speed, and Miss Kittin and the Hacker often used a hybrid approach to production that involves the integration of new(er) technologies, such as laptops containing various audio production softwares with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

Cross-dressing to Backbeats: An Exploration of the Practices, Wo/men Producers, and History of Electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.